Gambaran stres dan strategi emotion focus coping santri Asrama Bahasa Pondok Pesantren Salafiyah Syafi’iyah Sukorejo Situbondo - Kamila, Aisyatin; Hasanah, Faidatul (PSYCOMEDIA : Jurnal Psikologi, 2023)
Activities of students at Islamic boarding schools are busy and full of challenges. Moreover, activities in Islamic boarding schools with an education system that focuses on religion and general. Full activity routine from early morning until late at night. Moreover, students who live in special dormitories with the addition of English and Arabic in the dormitory where they live in Islamic boarding schools. Memorizing goals that must be achieved, speaking in the dormitory using English and Arabic, as well as academic and moral demands that must be achieved, are very potential for students to experience various psychological problems. This study aims to identify and describe the psychological problems faced by students who live in language dormitories at the Salafiyah Syafi'iyah Islamic boarding school, Sukorejo Situbondo, as well as coping strategies for dealing with existing problems. This research involved 7 students in the language dormitory who had been in the dormitory for at least 2 years with ages 17 and over. Data was collected through observation and interviews. The results of the study show that the language of boarding students in managing stress uses emotion focus coping strategies because they often divert problems and their stressors by creating problems. Activities of students at Islamic boarding schools are busy and full of challenges. Moreover, activities in Islamic boarding schools with an education system that focuses on religion and general. Full activity routine from early morning until late at night. Moreover, students who live in special dormitories with the addition of English and Arabic in the dormitory where they live in Islamic boarding schools. Memorizing goals that must be achieved, speaking in the dormitory using English and Arabic, as well as academic and moral demands that must be achieved, are very potential for students to experience various psychological problems. This study aims to identify and describe the psychological problems faced by students who live in language dormitories at the Salafiyah Syafi'iyah Islamic boarding school, Sukorejo Situbondo, as well as coping strategies for dealing with existing problems. This research involved 7 students in the language dormitory who had been in the dormitory for at least 2 years with ages 17 and over. Data was collected through observation and interviews. The results of the study show that the language of boarding students in managing stress uses emotion focus coping strategies because they often divert problems and their stressors by creating problems.